2012
DOI: 10.3390/s120911734
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Evaluation of Bluetooth Low Energy: An Emerging Low-Power Wireless Technology

Abstract: Bluetooth Low Energy (BLE) is an emerging low-power wireless technology developed for short-range control and monitoring applications that is expected to be incorporated into billions of devices in the next few years. This paper describes the main features of BLE, explores its potential applications, and investigates the impact of various critical parameters on its performance. BLE represents a trade-off between energy consumption, latency, piconet size, and throughput that mainly depends on parameters such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
408
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 767 publications
(464 citation statements)
references
References 19 publications
5
408
0
6
Order By: Relevance
“…Bluetooth is a wireless technology that is used for short-range data exchange and Wireless Personal Area Network (WPAN) (Mautz, 2012;Gomez, Oller, & Paradells, 2012;Y. Wang, Yang, Zhao, Liu, & Cuthbert, 2013).…”
Section: Bluetooth-based Positioning Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Bluetooth is a wireless technology that is used for short-range data exchange and Wireless Personal Area Network (WPAN) (Mautz, 2012;Gomez, Oller, & Paradells, 2012;Y. Wang, Yang, Zhao, Liu, & Cuthbert, 2013).…”
Section: Bluetooth-based Positioning Systemmentioning
confidence: 99%
“…Wang, Yang, Zhao, Liu, & Cuthbert, 2013). Gomez et al (2012), Y. Wang et al (2013), Rida, Liu, Jadi, Algawhari, and Askourih (2015) and Zhuang, Yang, Li, Qi, and El-Sheimy (2016), among other researchers, have used mobile WPAN that utilise the RSS feature in a couple of implementations that include positioning.…”
Section: Bluetooth-based Positioning Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Also limited battery life affects the above mentioned features through strict energy saving requirements (Vergara & Tehrani 2013, Hoque et al 2015. The use of sleep modes, for example, may significantly increase network latencies (Jurdak et al 2010, Gomez et al 2012, Ayoub et al 2011. However, major differences in the hardware capacity between peer nodes pose even a more substantial challenge for the P2P network functionality than the limited hardware capacity itself would inflict (Rao et al 2003, Kim & Park 2006.…”
Section: Challenges For Peer-to-peer Networking In Mobile Environmentmentioning
confidence: 99%
“…The studies showed that the energy consumption of ZigBee in idle state ranges from 52µW (120s sleep interval) to 1.45mW (5s sleep interval), the active state consumption is around 31mW, and data transfer consumption ranges from 3.3 to 9 µJ per byte when throughput varies between 8 bit/s and 80 kbit/s. Bluetooth Low Energy (BLE) is a low energy version of Bluetooth, specified in version 4.0 , Bluetooth 2014, Gomez et al 2012. The specification includes PHY layer, link layer (LL), logical link control and adaptation protocol (L2CAP), generic attribute protocol (GATT) and generic access profile (GAP) protocols.…”
Section: Short-range Networkmentioning
confidence: 99%